Natural resources and the spread of HIV/AIDS: curse or blessing? - Sterck, O (Elsevier, 2015)
This paper answers two questions: “What impact have natural resources had on the spread of the HIV epidemic so far?” and “What role can natural resource rents play in order to finance the long-run response to HIV/AIDS?” Using a panel dataset covering 137 countries from 1990 until 2008, de Soysa and Gizelis (2013) provided evidence in Social Science & Medicine that oil-rich countries are more deeply affected by the HIV and TB epidemics. They concluded that government of resource-rich countries failed to implement effective public policies for dealing with the epidemics. In this paper, I show that their results are (1) not robust, (2) based on an inappropriate choice of dependent variable and (3) spurious because series are non-stationary. After correcting for these issues, I find no robust relationship between resource rents and the spread of HIV and TB. The paper concludes by emphasizing the potential of natural resources rents for financing the long-term liability brought about by the HIV/AIDS epidemic in sub-Saharan Africa.